2016
DOI: 10.1038/ncomms12467
|View full text |Cite
|
Sign up to set email alerts
|

Subcompartmentalization by cross-membranes during early growth of Streptomyces hyphae

Abstract: Bacteria of the genus Streptomyces are a model system for bacterial multicellularity. Their mycelial life style involves the formation of long multinucleated hyphae during vegetative growth, with occasional cross-walls separating long compartments. Reproduction occurs by specialized aerial hyphae, which differentiate into chains of uninucleoid spores. While the tubulin-like FtsZ protein is required for the formation of all peptidoglycan-based septa in Streptomyces, canonical divisome-dependent cell division on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 43 publications
3
38
0
2
Order By: Relevance
“…Consistent with this notion, the chromosome segregation proteins ParAB in this organism is able to regulate cell tip elongation and FtsZ assembly (30, 76), and the broadly conserved multi-functional cell division protein DivIVA interacts with ParA at least indirectly via a cytoskeletal protein Scy (29, 62). Finally, it is worth noting that, although most of the cell division research in S. coelicolor has been focused on sporulation in this organism due to the dispensability of ftsZ during normal growth, new observations suggest that this naturally filamentous bacterium does indeed routinely separate its cytosol and achieve compartmentalization by formation of FtsZ-independent “cross-membranes” that represent a form of cell division whose molecular details of formation and regulation await further study (23, 143). …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this notion, the chromosome segregation proteins ParAB in this organism is able to regulate cell tip elongation and FtsZ assembly (30, 76), and the broadly conserved multi-functional cell division protein DivIVA interacts with ParA at least indirectly via a cytoskeletal protein Scy (29, 62). Finally, it is worth noting that, although most of the cell division research in S. coelicolor has been focused on sporulation in this organism due to the dispensability of ftsZ during normal growth, new observations suggest that this naturally filamentous bacterium does indeed routinely separate its cytosol and achieve compartmentalization by formation of FtsZ-independent “cross-membranes” that represent a form of cell division whose molecular details of formation and regulation await further study (23, 143). …”
Section: Introductionmentioning
confidence: 99%
“…MatAB proteins have an uncharacterised role in glycan production 54 . Vesicular membrane structures form in apparently irregular locations within hyphae, and some of them extend across the hyphal compartment, separating nucleoids 57, 58 .…”
Section: Ecology and Evolutionmentioning
confidence: 99%
“…The recent application of advanced microscopic methods has suggested that vesicular, DNA-impermeable membranous structures may delimit compartments in vegetative hyphae in the absence of conventional septa, may account for the viability of some hyphal fragments of ftsZ mutants, and may be implicated in the heterogeneous staining of vegetative hyphae with vital stains (interpreted as programmed death 56– 58 ) ( Figure 2). These intriguing observations raise questions of how the structures are placed in time and space, how they affect the spread of plasmids through the mycelium (see above), and whether they might limit the spread of initially tip-localised phage infections.…”
Section: New Perspectives In Growth and Development Of Streptomycesmentioning
confidence: 99%
“…Additionally, it remains unclear which environmental factors serve as cues for differentiation, and whether different strains vary in these responses to these cues. Despite the considerable differences between filamentous bacteria and fungi, their convergent morphologies suggest that similar divisions of labor may have evolved in both groups to reduce the costs and increase the efficiency of secreted products, especially given recent results conclusively demonstrating effective cytoplasmic streaming in streptomycetes (Celler et al, 2016; Yagüe et al, 2016). …”
Section: Divisions Of Labor Beyond Sporulationmentioning
confidence: 99%